The Footprint and sustainability of Private Higher Education Institutions in South Africa - Alan Bird; Virimai Mugobo (Tarbiyah Departement collaboration with AMCA, 2021)
The current Private Higher Education Institution (PHEI) landscape in South Africa is developing rapidly, with over ninety private tertiary institutions registered with the Council for Higher Education (CHE). However, stakeholder perceptions of these PHEIs are generally negative, primarily due to the negative perceptions of the qualification obtained from the private institutions by both parents and students and questions around the sustainability of the institutions in the long run. Media reports, lack of Department of Education (DHET) support and funding, and minimum, if any, marketing and advertising from the PHEI are factors cited for these firmly entrenched perceptions from the general public. Both emerging and international markets drove the article, countries such as Singapore, Malaysia, India and Brazil; not as a comparative study, but more as a literature review on how tertiary education is managed in the private sector in these countries. In addition, developing countries and emerging markets needed to be considered in light of their experience in sustaining private education entities. The subsequent investigation of these markets proved invaluable in terms of providing similarities and, in some instances, huge differences, which contributed to establishing the critical drivers for sustaining PHEIs in South Africa. Knowing which dimensions the branding of a PHEI should focus on nullifying the negative perceptions associated with a PHEI is paramount.